Analisis Data Perencanaan untuk Sistem Pengolahan Sampah Kampus Universitas Andalas Limau Manis Padang - Yenni Ruslinda; Nilda Tri Putr; Regina Mardatillah; Febri Kurnia Mulya (Jurnal Serambi Engineering, 2024)
The waste processing performance at the Integrated Waste Processing Center of Andalas University has experienced a decline; therefore, an evaluation and development of the waste processing system are needed. This research aims to analyze planning data for the waste processing system, including waste generation analysis, composition, recycling potential, and waste characteristics. Waste samples were taken from 48 campus facilities representing office activities, academic activities, student activities, and other activities. Waste generation, composition, and recycling potential analyses were conducted in the field using gravimetric methods, while characteristic analyses were performed in the laboratory.From the research results, planning data for the campus waste generation unit was obtained at 0.0592 kg/person/hour or 0.00163 kg/m²/hour, and in volume units, it was 0.5245 liters/person/hour or 0.02945 liters/m²/hour. The waste composition consisted of 49.61% easily decomposable waste, 38.22% recyclable waste, 1% hazardous waste (B3), and 16.21% residual waste. The potentially recyclable waste includes food waste, yard/wood waste, plastic, paper, glass, and metal, with an average potential of 89%. Waste characteristics include a specific gravity of 0.058, moisture content of 22.18%, volatile matter content of 59.95%, fixed carbon content of 12.09%, ash content of 5.79%, C/N ratio of 30.28, biodegradability of 54.06%, and a fly population of 2 flies/m².Campus waste has the potential to be processed through composting, Black Soldier Fly (BSF) bioconver sionand biodrying for easily decomposable waste, and it can be sold to the informal sector for recycling.